2020
DOI: 10.1111/ijlh.13188
|View full text |Cite
|
Sign up to set email alerts
|

Hemolysis interference in 10 coagulation assays on an instrument with viscosity‐based, chromogenic, and turbidimetric clot detection

Abstract: Introduction: Hemolysate in plasma samples from patients may cause misleading results in coagulation assays. Even though modern coagulation instruments often are equipped with modules that can detect hemolysis, icterus, and lipemia (HIL), studies that report the influence of these interferences are still limited. The present paper focuses on the influence of hemolysis on 10 coagulation assays.Methods: Artificial hemolysis was created by freezing/thawing, and the hemolysates generated were added to pools of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
3
5
0
Order By: Relevance
“…The data in this study have demonstrated a good correlation in results between normal and spiked haemolysed plasma samples in PT, APTT, Clauss fibrinogen and TT with the observed overall difference between the means for two samples within 5% for all four tests. Data for PT obtained in this study which compared normal and spiked haemolysed lyophilized plasma appeared to be in line with previous findings which used spiked fresh or frozen plasma where PT was insignificantly influenced by haemolysis 17‐20 . A statistical difference between the means of two samples was noted in ACL TOP user group which used IL HemosIL RecombiPlasTin 2G method.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The data in this study have demonstrated a good correlation in results between normal and spiked haemolysed plasma samples in PT, APTT, Clauss fibrinogen and TT with the observed overall difference between the means for two samples within 5% for all four tests. Data for PT obtained in this study which compared normal and spiked haemolysed lyophilized plasma appeared to be in line with previous findings which used spiked fresh or frozen plasma where PT was insignificantly influenced by haemolysis 17‐20 . A statistical difference between the means of two samples was noted in ACL TOP user group which used IL HemosIL RecombiPlasTin 2G method.…”
Section: Discussionsupporting
confidence: 90%
“…Comparable data received for the overall means for two samples in Clauss fibrinogen testing suggest that haemolysis does not have potential to cause major changes on test result. Previous comparison studies with the use of genuine haemolysed or spiked fresh plasmas reported analogous results for fibrinogen 3,20,21 . The tendency for higher per cent difference which was also statistically significant between two samples was obvious within the Sysmex platform group which used Siemens Thrombin reagent.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The effect of hemolysis was most pronounced on the DRVVT Screen and DRVVT Ratio, with the potential to cause a false‐negative lupus anticoagulant test result by this methodology when the H index approached or exceeded 500 mg/dL. The effect of hemolysis on the other assays evaluated was considered minimal (≤15% bias) up to a plasma hemoglobin concentration of 900 mg/dL, which is similar to other reports, 11,12 although a progressive shortening of the PT and APTT was observed with both the optical and mechanical platforms, likely reflecting a biological effect of hemolysis on clot activation. Several methods have been proposed for studying the effects of hemolysis on coagulation assays, including paired hemolyzed and nonhemolyzed samples collected at different times from the same patient and in vitro spiking studies using hemolysate prepared by freeze‐thaw, osmotic shock, or shearing with multiple needle aspirations, each method having its own limitations 13,14 .…”
Section: Discussionsupporting
confidence: 82%
“…In this study, no significant impact of hemolysis was found up to hemoglobin concentrations of 10 g/L, which was higher compared with the manufacturers’ data (Table 2) and previous studies on other assays. For instance, a recent study performed with the STA‐Liatest D‐Di Plus reagent on a STAR MAX 2 analyzer found that D‐dimer values started to increase from 6 g/L of hemoglobin 26 27 who found no significant change in D‐dimer concentrations up to 300 mg/L of bilirubin.…”
Section: Discussionmentioning
confidence: 99%